The Protection of Creditor’s Right and Actio Pauliana - Siti Anisah (Fakultas Hukum Universitas Islam Indonesia, 2009)
In general, the proving of actio pauliana is not simple, and the procces itself is not organized well. For the reasons, in order to make the protection of creditors’ right through actio pauliana is applicable, then we need implementative procedure provision concerning to actio pauliana.Keywords: Creditors’ Right; Actio Pauliana.